PREVENTION AND RELEVANCE OF CRIME AGAINST LGBTQ+ IN CONTEMPORARY INDIA - Sharan Kumar (Journal of Social Political Sciences, 2024)
The acronym LGBTQ+ originated in the mid-20th century, evolving from the term "homosexual," which was commonly used to describe same-sex attraction but often carried derogatory connotations. As the gay rights movement gained momentum during the 1960s and 1970s, the LGBTQ+ community adopted more inclusive and self-affirming terminology, with "gay" becoming widely accepted by the 1960s. By the 1970s, the acronym "LGBT" (lesbian, gay, bisexual, and transgender) was established, later expanding to include other identities such as queer, questioning, intersex, and asexual. This expansion reflects the growing recognition of diverse gender and sexual identities. This paper aims to explore the prevention and relevance of crimes against LGBTQ+ individuals in contemporary India, focusing on the ongoing challenges faced by the community and proposing strategies to address these issues. The study employs a qualitative approach, utilizing a combination of literature review and case study analysis to investigate the subject matter. The findings indicate that LGBTQ+ individuals in India continue to face significant challenges, including discrimination, violence, and inadequate legal protection. Key areas for intervention include legal reforms, public education, and the establishment of community support systems. The study underscores the importance of a multifaceted approach to addressing crimes against LGBTQ+ individuals in India, recommending comprehensive legal and social strategies to protect the rights and well-being of the LGBTQ+ community.